Human nature in Gregory of Nyssa: philosophical background and theological significance - Zachhuber, Johannes (Supplements to Vigiliae Christianae, 1999)
Preliminary Material -- Introduction -- Introduction -- 1. Homoousios and the Analogy of Human Nature in the 350s and Early 360s -- 2. The Cappadocian Teaching -- 3. Human Nature and the Theological Requirements of Salvation History -- 4. Gregory’s Teaching on Creation and Fall of Humanity -- 5. Human Nature in Gregory’s Soteriology and Eschatology -- Conclusion -- Bibliography -- Index of Biblical References -- Index of Ancient Authors -- Index of Modern Authors -- General Index.